Community Education Through Posyandu Activities and Supplementary Feeding (PMT) for Stunting Prevention in RW 02, Langensari Village, Garut Regency - Iwan Satibi; Thoriq Ramadhan Nursalam; Nabila Anindiya Andini; Gina Tiara Oktaviani; Rita Kamila (Transpublika Publisher, 2025)
This Community Service Programme (PKM) was carried out by students from the Faculty of Social and Political Sciences, Pasundan University, Bandung, at the Merpati RW 02 Health Post in Langensari Village, Tarogong Kaler Subdistrict, Garut Regency. This activity focused on educating the community through routine Integrated Health Service Post activities and providing supplementary food (PMT) to combat stunting in toddlers. The main problems identified included low nutritional intake among children, a lack of understanding among parents about health and nutrition, limited health facilities, and low community participation in immunisation. Through this PKM, balanced nutrition education was provided, and nutritious supplementary foods such as milk, whole wheat bread, and sausages were distributed. The implementation method consisted of three stages: preparation (observation and problem formulation), implementation (socialisation and PMT provision), and monitoring-evaluation. This activity successfully involved 43 toddlers and their parents. The results of the activity showed an increase in community understanding of the importance of preventing stunting and child nutrition. The outputs of the activity included increased community awareness of child health, activity reports, scientific articles for publication, and plans to register intellectual property rights. It is recommended that Integrated Health Service Post activities be strengthened through support from village government facilities, ongoing nutrition campaigns, and innovative educational activities to maintain high community interest.